Pengaruh Soft Skill, Efikasi Diri, dan Keaktifan Berorganisasi terhadap Kesiapan Kerja Mahasiswa Tingkat Akhir Program Studi Manajemen Universitas Dian Nuswantoro - Puspitasari, Aprilia Icha; Febriana, Artha; Purwatiningsih, Aris Puji; Perdana, Tito Aditya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Work readiness is a condition in which an individual possesses the abilities, knowledge, attitudes, and skills required to enter the workforce. It serves as a bridge between the world of education and industry. Based on tracer study data from Universitas Dian Nuswantoro, approximately 64.7% of alumni over the past five years have not yet been employed or engaged in entrepreneurship, indicating that students’ work readiness remains a significant challenge. This study aims to analyze the influence of soft skills, self-efficacy, and organizational activeness on the work readiness of final-semester students in the Management Study Program at Universitas Dian Nuswantoro, batch 2022. The research population consisted of 558 management students, with a sample of 125 respondents selected using purposive sampling techniques. The study employed a quantitative approach with a survey design, collecting data through Likert-scale questionnaires and analyzing them using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Soft skills, self-efficacy, and organizational activeness collectively explain 78% of the variance in students’ work readiness (R-square = 0.780). The results indicate that soft skills, self-efficacy, and organizational activeness have a significant positive effect on work readiness, demonstrating that these three independent variables enhance students’ professional work readiness.